Synergistic Integration of Land and Sea Transportation: Realizing Oosthaven as a Strategic Port City at the Tip of Sumatra - Aprilia Triaristina; Valensy Rachmedita (Swarnadwipa, 2026)
This study discusses the development of Oosthaven Port and the importance of integrating land and sea transportation in making it a strategic port city at the southern tip of Sumatra. The primary focus of this research is to analyze how the development of this port was driven by Dutch colonial policies that emphasized the control of trade in key commodities such as pepper, coffee, and rubber. Additionally, the study examines the role of land transportation through the construction of railway lines connecting the port to inland areas, thus facilitating the distribution of commodities to international markets. Oosthaven, which initially served as a simple port, evolved into a crucial trade hub due to the efficient coordination of land and sea transportation infrastructure. This research shows that the development and management of transportation integration at Oosthaven not only accelerated the economic growth of the Lampung region but also reflected the influence of colonial policies in regulating and dominating the trade system, while introducing a social structure that prioritized segregation based on class and ethnicity.